The purity of vengeance - Adler-Olsen, Jussi; Aitken, Martin (New York : Dutton, 2016)
"In 1987, Nete Hermansen plans revenge on those who abused her--especially Curt Wad, a surgeon who was part of a movement to sterilize wayward girls in the 1950s. More than twenty years later, Detective Carl Morck already has plenty on his mind when he is presented with the case of a brothel owner, a woman named Rita, who went missing in the eighties: New evidence has emerged in the case that sent Carl to Department Q. But when Carl's assistants, Assad and Rose, learn that numerous other people disappeared around the same weekend as Rita, Carl takes notice. Sifting through the evidence, they inch closer to Curt Wad, who is still committed to his twisted beliefs, and whose treatment of Nete only hints at his capacity for evil."--Cover
Keywords: Missing persons -- Investigation -- Fiction; Detective and mystery fiction